Cosplay Adolescent Community in Padang City(Case Study: White Raven Community) - Erningsih Erningsih (LPPM Universitas PGRI Sumatera Barat, 2019)
Individuals become part of the community by following the rules in the community so that it is inherent inthemselves. One of the popular cultural communities in the city of Padang is a Cosplay community whose members consist of teenagers. One of them is the White Raven Cosplay community. The research aims to describe the Cosplay community in Padang City (Case study: White Raven Community). Data in this study were conducted and collected through interviews, observations and document studies. This study found that adolescents who joined in the community, despite having a busy schedule both at home and school, but they remained actively in this community. Moreover this cosplay community is a place to carve achievements and make many new friends, become the center of attention, increase self-confidence, and become an arena of creativity for them.